Preparation and Characterizationof Palm-Based Functional Lipid Nanodispersions - Cheong, Jean Ne (2008)
Poor solubility of functional lipids has made their use problematic in food industry especially in food formulations. The difficulties to find a suitable formulation or solution are even greater especially when the functional lipids are poorly soluble in both aqueous and organic solutions, which may prone to reduce bioavailability. The main objective of this study was to prepare and characterize palm-based functional lipids nanodispersions. The observations presented in this study confirmed that the nanosized droplets formed using emulsification-evaporation is relatively simple and effective technique especially for producing nanodispersions of palm-based functional lipids (tocopherols-tocotrienols and carotenoids). Droplet size can be produced in a controlled way by adjusting the processing parameters such as pressure and cycle number accordingly. This study indicated that by increasing the energy input beyond moderate pressures (20 – 80 MPa) and cycles (1 - 3) led to “overprocessing” of droplets. Results have revealed that homogenization pressures have significant (P < 0.05) influence on the average droplet size and droplet size distribution (PI). On the contrary, the processing cycle had not significantly effect the average droplet size and size distribution (P > 0.05). Preliminary studies have shown droplet diameters in the range of 90 - 120 nm for prepared α-tocopherol nanodispersions. Meanwhile, nano-droplet resulted from nanodispersions prepared with palm-based functional lipids extended from 95 – 130 nm and 140 – 210 nm for tocopherols-tocotrienols and carotenoids, respectively. During storage duration, all prepared nanoemulsions showed good physical stability. However, the content of the prepared nanodispersions was significantly (P < 0.05) reduced during storage. Investigation on the effect of polyoxyethylene sorbitan esters and sodium caseinate also revealed that the average droplet size significantly (P < 0.05) increased with increasing chain length of fatty acid and increasing the HLB value. Among the prepared nanodispersions, the palm-based tocopherols-tocotrienols nanodispersions containing Polysorbate 20 illustrated the smallest average droplet sizes and narrowest size distribution (201.8 ± 1.4 nm; PI, 0.399 ± 0.022); while palm-based carotenoids nanodispersions containing sodium caseinate had the largest average droplet size (386.3 ± 4.0nm; PI, 0.465 ± 0.021); thus indicating more emulsifying role induced by Polysorbate 20 compared to sodium caseinate.